Analisis Pengaruh Dimensi Fraud Analisis Pengaruh Dimensi Fraud Diamond Terhadap Perilaku Kecurangan Mahasiswa Akuntansi - Durya, Ngurah (CV. Kalimasada Group, 2023)
Disclosure of fraud by accounting students uses the Diamond Fraud concept. This study aims to determine the effect of the Fraud Diamond aspect on academic fraud in the student environment. In this study, the research sample was 80 students of the Muhammadiyah University of Surakarta accounting study program. Multiple regression analysis was used to examine the combined and individual effects of the independent variables on the dependent variable. This analysis is preceded by traditional assumption tests, which include normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests. While the F test and t test are used for hypothesis testing. The results of the research show that pressure has an effect on fraud, rationalization has an effect on fraud and ability has an effect on fraud, while opportunity has no effect on fraud. Suggestions that can be recommended are the importance of prioritizing ethical principles and social values in the academic environment